A CuO / MoS 2 / CuMoO 4 Preparation method and application of multi-level structure nanocomposite materials

Through the preparation of CuO/MoS2/CuMoO4 multi-stage structural nanocomposites, the problems of poor gas sensitivity and high test temperature of MoS2-based composites are solved, and good selectivity and stability response to H2S gas is achieved, and the stability and detection efficiency of the sensor are improved.

CN117985752BActive Publication Date: 2025-03-14ZHONGYUAN ENGINEERING COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410135048.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2025-03-14
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

MoS2-based composites have problems with poor gas sensitivity and excessive test temperature, and the sensor stability is poor.

Method used

CuO/MoS2/CuMoO4 multi-level structural nanocomposite was used to prepare a flower-like MoS2 nanomaterial composed of two-dimensional sheets by hydrothermal method. With microwave assistance, copper acetate was used as the precursor to uniformly cover CuO nanoparticles, and calcined in the air to form CuO/MoS2/CuMoO4 multi-level structural nanocomposite.

Benefits of technology

It improves gas sensing performance, especially good selectivity and stable response to H2S gas, reduces detection temperature, and improves the stability of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117985752B_ABST
    Figure CN117985752B_ABST
Patent Text Reader

Abstract

The present invention proposes a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material and its preparation method and application, which belongs to the technical field of material synthesis and is used to solve the technical problem of poor gas sensing performance of MoS2-based composite materials. The preparation method of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material in the present invention comprises the following steps: dissolving and mixing a molybdenum source and a sulfur source in a solvent I, adjusting the pH, and obtaining a flower-shaped molybdenum disulfide composed of two-dimensional sheets through a hydrothermal reaction; dispersing and dissolving molybdenum disulfide and a copper source in a solvent II, reacting under microwave-assisted conditions, washing and drying the product; calcining the dried product in air to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material. The H2S gas sensor made of the CuO / MoS2 / CuMoO4 multi-level structure composite material of the present invention has good gas sensing performance. The optimal operating temperature of the sensor for H2S gas is 240°C, and the sensor also has the advantages of fast reaction and recovery speed, large response value, and good long-term stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material synthesis, and in particular relates to a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material and a preparation method and application thereof. Background Art

[0002] With the development and progress of modern science and technology, people's living standards are improving, social production is becoming more industrialized, and air quality issues are receiving more and more attention. In order to ensure the safety of people's lives and property, the detection of toxic and harmful gases in the air has become a key issue for scientists. Excellent sensors should have the characteristics of high sensitivity, good selectivity, strong stability, etc., and should be able to withstand harsh working conditions. Although the gas chromatography method we are familiar with can detect harmful pollutants in life with high precision, compared with sensors based on metal oxide semiconductors, these methods are not very suitable for real-time monitoring. The main working mechanism of resistive sensors is based on the change in resistance of the sensing layer such as metal oxide semiconductors when it contacts the analytical gas, and has the advantages of small size, simple structure, light weight, low power consumption, low cost, etc., and has developed rapidly.

[0003] Molybdenum disulfide has a layered structure, a large specific surface area, unique mechanical properties, chemical and electrical properties, which make it occupy a place in the field of gas detection resistor sensors. In particular, various three-dimensional layered MoS2 nanostructures composed of low-dimensional nano-sized structures have smaller material diffusion sizes, more sensitive electronic characteristics and richer chemical active sites than traditional nanocrystals, and are considered to be the most promising gas-sensitive materials. Therefore, the research and development and preparation of various three-dimensional layered MoS2 nanomaterials with completely different shapes have become the focus of research and development. In addition, the use of heterogeneous structures can also solve some problems existing in single gas-sensitive materials, which is of great significance for improving the gas-sensitive properties of materials such as metal oxide semiconductors. Therefore, by designing and preparing heterogeneous structures of composite materials composed of MoS2 and p-type metal oxide semiconductors, it is expected to achieve better gas sensing performance. Summary of the invention

[0004] In view of the technical problems of poor gas sensing performance and high test temperature of MoS2-based composite materials, the present invention proposes a CuO / MoS2 / CuMoO4 multi-level structure nano-composite material and its preparation method and application. The H2S gas sensor made of the CuO / MoS2 / CuMoO4 multi-level structure composite material has good gas sensing performance.

[0005] In order to achieve the above object, the technical solution of the present invention is implemented as follows:

[0006] A method for preparing a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material comprises the following steps:

[0007] (1) dissolving and mixing a molybdenum source and a sulfur source in a solvent I, adjusting the pH, and obtaining molybdenum disulfide through a hydrothermal reaction;

[0008] (2) dispersing and dissolving molybdenum disulfide and a copper source in solvent II, reacting under microwave-assisted conditions, and washing and drying the product;

[0009] (3) The dried product is calcined in air to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0010] The molybdenum source is sodium molybdate; the sulfur source is thiourea; and the solvent I is water or ethanol.

[0011] The molar ratio of the molybdenum source to the sulfur source is 1:(3-5); the concentration of the molybdenum source in solvent I is 0.01-0.1 mmol / ml.

[0012] The reagent used for adjusting the pH is concentrated hydrochloric acid, and the pH is adjusted to 1.5-2.5; the temperature of the hydrothermal reaction is 160-230° C., and the reaction time is 12-24 hours.

[0013] The copper source is copper acetate; the solvent II is water or ethanol.

[0014] In the step (2), the mass ratio of molybdenum disulfide to copper source is 1:(1-12); the concentration of molybdenum disulfide in solvent II is 0.05-0.2 mmol / ml.

[0015] The microwave-assisted conditions are: reaction temperature of 80° C.-110° C., microwave power of 100-1000 W, and time of 1-20 minutes.

[0016] The calcination temperature is 450-700° C. and the calcination time is 0.5-5 h.

[0017] Application of a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material in gas concentration detection.

[0018] Beneficial effects of the present invention:

[0019] Flower-like MoS2 nanomaterials composed of two-dimensional sheets were prepared by hydrothermal method. Under microwave-assisted conditions, copper acetate was used as a precursor, and no precipitant was added to prepare a CuO / MoS2 nanocomposite intermediate in which a large number of CuO nanoparticles were uniformly covered on the surface of the flower-like MoS2. Finally, the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite was generated by calcination in air. During calcination, CuO and MoS2 reacted at the interface to generate CuMoO4, which acted as a protective film, so that the CuO / MoS2 / CuMoO4 nanocomposite maintained the main morphology of the flower-like MoS2 due to the presence of a thin layer of MoS2 in the inner layer, and the unreacted CuO was most evenly distributed, which means that more CuO / CuMoO4 and MoS2 / CuMoO4 heterojunction interfaces were provided as active sites and adsorption sites per unit mass for gas adsorption, electron transport and reaction, which is very beneficial to improve the interaction between gas and composite materials, thereby improving gas sensing performance. Calcination in air can solve the disadvantage of poor gas sensitivity of MoS2; after calcination in air, MoS2 reacts with oxygen in the air at high temperature to generate MoO3 and release heat, and at the same time, it reacts with CuO particles uniformly attached to the surface of MoS2 petal layer under microwave to generate CuMoO4; in addition, the SO2 and H2O gases released during the reaction create a large number of pores, which are conducive to the improvement of gas sensing performance. In summary, the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material obtained by the above green preparation method has good selectivity and stability response to H2S gas, which is of great significance for effectively solving the problems of too high detection temperature and poor stability of gas sensors in previous gas sensing detection. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a SEM electron microscope image of MoS2 prepared in Example 4; in the figure, (a) is a low-magnification SEM image; (b) is a high-magnification SEM image.

[0022] Figure 2 SEM images of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material prepared in Example 4; in the figure, (a) is a low-magnification SEM image; (b) is a high-magnification SEM image.

[0023] Figure 3XRD image of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material prepared in Example 4.

[0024] Figure 4 The gas-sensitive response-time dynamic change curve of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material to H2S prepared in Example 4.

[0025] Figure 5 The sensitivity and temperature relationship image of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material prepared in Example 4 to H2S at different concentrations.

[0026] Figure 6 The response recovery time images of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material prepared in Example 4 at various temperatures.

[0027] Figure 7 Selective images of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material prepared in Example 4 for different gases. DETAILED DESCRIPTION

[0028] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method specifically comprises the following steps:

[0031] (1) Dissolve 1.6 mmol of sodium molybdate and 8 mmol of thiourea in 40 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 2 with HCL;

[0032] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 210° C., the reaction time was 12 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0033] (3) Disperse 0.8 g of molybdenum disulfide in 50 mL of water, add 1 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0034] (4) The suspension was then placed in a 400 W microwave oven and set to a boiling temperature of 95°C for irradiation reaction for about 2 minutes until boiling and then continued to boil for another 3 minutes. After naturally cooling to approximately 25°C, the black precipitate was collected by centrifugation, washed several times with distilled water, and dried.

[0035] (5) The dried product was placed in a crucible and calcined at 550° C. in an air atmosphere for 2.5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0036] Example 2

[0037] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method of which comprises the following steps:

[0038] (1) Dissolve 1.6 mmol of sodium molybdate and 8 mmol of thiourea in 40 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 2 with HCL;

[0039] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 210° C., the reaction time was 12 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0040] (3) Disperse 0.64 g of molybdenum disulfide in 50 mL of water, add 1.2 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0041] (4) The suspension was then placed in a 400 W microwave oven and set to a boiling temperature of 95°C for irradiation reaction for about 2 minutes until boiling and then continued to boil for another 3 minutes. After naturally cooling to approximately 25°C, the black precipitate was collected by centrifugation, washed several times with distilled water, and dried.

[0042] (5) The dried product was placed in a crucible and calcined at 600° C. in an air atmosphere for 2.5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0043] Example 3

[0044] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method of which comprises the following steps:

[0045] (1) Dissolve 1.6 mmol of sodium molybdate and 8 mmol of thiourea in 40 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 2 with HCL;

[0046] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 210° C., the reaction time was 12 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0047] (3) Disperse 0.48 g of molybdenum disulfide in 50 mL of water, add 1.4 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0048] (4) The suspension was then placed in a 400 W microwave oven and set to a boiling temperature of 95°C for irradiation reaction for about 2 minutes until boiling and then continued to boil for another 3 minutes. After naturally cooling to approximately 25°C, the black precipitate was collected by centrifugation, washed several times with distilled water, and dried.

[0049] (5) The dried product was placed in a crucible and calcined at 550° C. in an air atmosphere for 2.5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0050] Example 4

[0051] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method of which comprises the following steps:

[0052] (1) Dissolve 1.6 mmol of sodium molybdate and 8 mmol of thiourea in 40 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 2 with HCL;

[0053] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 210° C., the reaction time was 12 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0054] (3) Disperse 0.32 g of molybdenum disulfide in 50 mL of water, add 1.6 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0055] (4) The suspension was then placed in a 400 W microwave oven and set to a boiling temperature of 95°C for irradiation reaction for about 2 minutes until boiling and then continued to boil for another 3 minutes. After naturally cooling to approximately 25°C, the black precipitate was collected by centrifugation, washed several times with distilled water, and dried.

[0056] (5) The dried product was placed in a crucible and calcined at 550° C. in an air atmosphere for 2.5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0057] Example 5

[0058] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method of which comprises the following steps:

[0059] (1) Dissolve 1.6 mmol of sodium molybdate and 8 mmol of thiourea in 40 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 2 with HCL;

[0060] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 210° C., the reaction time was 12 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0061] (3) Disperse 0.16 g of molybdenum disulfide in 50 mL of water, add 1.8 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0062] (4) The suspension was then placed in a 400 W microwave oven and set to a boiling temperature of 95°C for irradiation reaction for about 2 minutes until boiling and then continued to boil for another 3 minutes. After naturally cooling to approximately 25°C, the black precipitate was collected by centrifugation, washed several times with distilled water, and dried.

[0063] (5) The dried product was placed in a crucible and calcined at 500° C. in an air atmosphere for 2.5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0064] Example 6

[0065] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method of which comprises the following steps:

[0066] (1) Dissolve 1.6 mmol of sodium molybdate and 4.8 mmol of thiourea in 160 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 1.5 with HCl;

[0067] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 160° C., the reaction time was 24 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0068] (3) Disperse 0.8 g of molybdenum disulfide in 100 mL of water, add 1 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0069] (4) The suspension is then placed in a 1000 W microwave oven and set to a boiling temperature of 80° C. for irradiation reaction for about 2 minutes until boiling, and then continued to boil for another 3 minutes. After naturally cooling to approximately 25° C., the black precipitate is collected by centrifugation, washed multiple times with distilled water, and dried.

[0070] (5) The dried product is placed in a crucible and calcined at 700° C. in an air atmosphere for 0.5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0071] Example 7

[0072] A CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, the preparation method of which comprises the following steps:

[0073] (1) Dissolve 1.6 mmol of sodium molybdate and 6.4 mmol of thiourea in 16 ml of deionized water, and continue stirring for 10 minutes to completely dissolve the sodium molybdate and thiourea. Adjust the pH value of the solution to 2.5 with HCl.

[0074] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 230° C., the reaction time was 16 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0075] (3) Disperse 0.8 g of molybdenum disulfide in 25 mL of water, add 1 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0076] (4) The suspension was then placed in a 100 W microwave oven and set to a boiling temperature of 110° C. for irradiation reaction for about 20 minutes until boiling and then continued to boil for another 3 minutes. After naturally cooling to approximately 25° C., the black precipitate was collected by centrifugation, washed several times with distilled water, and dried.

[0077] (5) The dried product was placed in a crucible and calcined at 300° C. in an air atmosphere for 5 h to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material.

[0078] Comparative Example 1

[0079] A CuO / MoS2 nanocomposite material, the preparation method comprises the following steps:

[0080] (1) Dissolve 1.6 mmol of sodium molybdate and 8 mmol of thiourea in 40 ml of deionized water, stir for 10 minutes to completely dissolve the sodium molybdate and thiourea, and adjust the pH value of the solution to 2 with HCL;

[0081] (2) The prepared solution was transferred to a reactor with a volume of 50 ml, the reaction temperature was controlled to be 210° C., the reaction time was 12 h, and after the reaction was completed, it was naturally cooled to room temperature, and the reactants were collected by centrifugation, centrifuged, washed, and dried to obtain molybdenum disulfide;

[0082] (3) Disperse 0.32 g of molybdenum disulfide in 50 mL of water, add 1.6 g of copper acetate, and stir in a conical flask for half an hour to form a uniform suspension.

[0083] (4) The suspension was then placed in a 400 W microwave oven and set to a boiling temperature of 95° C. for irradiation reaction for about 2 minutes until boiling and then continued to boil for 3 minutes. After naturally cooling to nearly 25° C., the black precipitate was collected by centrifugation, washed with distilled water for multiple times, and dried to obtain a CuO / MoS2 nanocomposite material.

[0084] Application Examples

[0085] Take the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite prepared in Example 1 as an example to make a gas sensor. Pour a little sample from a plastic conical tube, place the sample in an agate mortar rinsed with deionized water and free of impurities, grind the sample into fine powder with the handle of the mortar rinsed with deionized water and free of impurities, and add some anhydrous ethanol to grind it again, ensuring that the grinding is sufficient to a paste, and use a clean small fine brush to evenly apply the sample on the alumina ceramic tube with platinum wire, requiring that the sample thickness applied on the alumina ceramic tube with platinum wire is uniform, and the drug cannot be contaminated on the resistance wire. Then use a thinner pair of tweezers to clamp the nickel-chromium resistance wire and carefully insert it into the alumina ceramic tube, be sure to avoid pulling during the process to prevent damage to the resistance wire, and then use soldering to weld the platinum wire and the resistance wire in turn to the corresponding positions of the six-pin tube seat to make a gas sensor. The above method is used to sequentially make the gas sensors corresponding to the samples prepared in Examples 2-5 and Comparative Example 1.

[0086] Test Case

[0087] Figure 1 This is the SEM electron microscope image of MoS2 prepared in step (2) in Example 4. It can be seen that the flower-like structure composed of two-dimensional flakes is very obvious and has advantages such as a large specific surface area.

[0088] Figure 2 The SEM images of CuO / MoS2 / CuMoO4 multi-level structure nanocomposites; in the figure, (a) is a low-magnification SEM image; (b) is a high-magnification SEM image. It can be clearly observed that most of the CuO / MoS2 / CuMoO4 flower-like multi-level structures Figure 1It can be seen from the images (a) and (b) that during the preparation process, CuO / MoS2 / CuMoO4 inherited the good morphology and large specific surface area of ​​MoS2. In the image (b), it can be clearly seen that small CuO / CuMoO4 particles are loaded on the sheet.

[0089] Figure 3 (a) is the XRD pattern of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite prepared in Example 4. The sharp characteristic peaks are consistent with the standard spectrum of CuMoO4 (b) JCPDS21-0293, the standard spectrum of MoS2 (c) JCPDS 0 2-1133, and the standard spectrum of CuO (d) JCPDS 02-1041, indicating that both CuO and CuMoO4 exist and have good crystallinity, and there is MoS2 remaining and not completely reacted. The main peaks of CuMoO4 are (201)(-202)(-302), the main peaks of MoS2 are (103)(105)(112), and the main peaks of CuO are (002)(200)(220).

[0090] Figure 4 The real-time sensitivity dynamic change curve of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite prepared in Example 4 to H2S gas of different concentrations, the test temperature is 240°C. Figure 4 It can be seen that the sensitivity of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material to H2S gas increases with the increase of H2S concentration. When the H2S concentration is 50ppm, the sensitivity of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material to H2S reaches 21. At the same time, when the test temperature is 240℃ and the H2S concentration is 50ppm, the sensitivity of CuO / MoS2 prepared in Comparative Example 1 is measured to be 6.

[0091] Gas-sensing performance test: The gas-sensing test uses the HW-30A gas-sensing element tester. The gas-sensing element prepared in the application example is inserted into the electronic board of the gas-sensing element tester. It is evaporated at 200°C for a while to ensure that the anhydrous ethanol in the gas-sensing element is evaporated cleanly. Then, it can be adjusted to 300°C for quality inspection and element aging of the gas-sensing element. By adjusting the heating voltage, the temperature operating range of the tester can be controlled. The load voltage at both ends of the test element can be changed by adjusting the load resistance, so as to achieve the purpose of testing the element at different temperatures. At different operating temperatures, the gas-sensing performance of H2S gas of different concentrations was systematically tested. The test temperatures are 160°C, 200°C, 240°C, 300°C, and 340°C respectively. The test concentrations of the target liquid are 0.1ppm, 0.5ppm, 1ppm, 5ppm, 10ppm, 25ppm, and 50ppm respectively.

[0092] Figure 5 The responses of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite prepared in Example 4 to H2S gas of different concentrations at different temperatures. At each temperature, the sensitivity increases with the increase of H2S gas concentration. The sensitivity of the gas of the same concentration increases first and then decreases with the increase of temperature. The preferred test temperature is around 240°C, which is better than the previous report that the temperature is usually above 340°C to achieve the best result, and has obvious advantages in low-temperature detection.

[0093] Figure 6 The response recovery time bar graph of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite prepared in Example 4 to H2S gas at different temperatures shows that the response recovery time basically meets the rule that as the temperature increases, the response speed increases. The response recovery time is as short as 4s at 340°C and 7s at 300°C.

[0094] Figure 7 The selectivity of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite prepared in Example 4 to H2S gas relative to other gases, wherein H2S is 25ppm and other gases are 100ppm. It can be seen from the figure that the selectivity of the composite material to H2S gas with a lower concentration is also better than that of other gases with a higher concentration.

[0095] With the addition of gas, the resistance of the CuO / MoS2 / CuMoO4 multi-level structure sample decreases rapidly after adsorbing H2S gas, and the resistance can be quickly restored after releasing H2S gas, and the corresponding recovery time is short. This is mainly due to the n-type semiconductor characteristics of the semiconductor gas sensor of the CuO / MoS2 / CuMoO4 multi-level structure composite material as a whole, that is, when the CuO / MoS2 / CuMoO4 multi-level structure composite material sensor is exposed to the air, oxygen molecules are adsorbed on the surface of the CuO / MoS2 / CuMoO4 multi-level structure composite material, and then by capturing free electrons on the conduction band of the material lattice, a relatively thick carrier depletion layer is generated on the surface of the CuO / MoS2 / CuMoO4 multi-level structure composite material, which ultimately increases the resistance of the sensor. At this time, because the pn heterojunction of the CuO / MoS2 / CuMoO4 multi-level structure adds a large number of depletion layers, the resistance of the sensor is increased. However, when the sensor is exposed to H2S gas, the adsorbed electrons react with the H2S molecules on the surface of the material, releasing the captured electrons back into the composite material, thereby reducing the depletion region and the resistance of the sensor. Therefore, the obvious change in the sensor resistance causes the electronic components made of the CuO / MoS2 / CuMoO4 multi-level structure composite material to produce higher gas sensitivity.

[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material, characterized in that: The following steps are involved: (1) dissolving and mixing a molybdenum source and a sulfur source in a solvent I, adjusting the pH, and obtaining a flower-like molybdenum disulfide having a two-dimensional sheet structure through a hydrothermal reaction; (2) dispersing and dissolving molybdenum disulfide and copper source in solvent II, reacting under microwave-assisted conditions, and washing and drying the product; (3) calcining the dried product in air to obtain a CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material; the molybdenum source is sodium molybdate; the sulfur source is thiourea; and the solvent I is water or ethanol; The molar ratio of the molybdenum source to the sulfur source is 1:(3-5); the concentration of the molybdenum source in solvent I is 0.01-0.1 mmol / ml; The reagent used for adjusting the pH is concentrated hydrochloric acid, and the pH is adjusted to 1.5-2.5; the temperature of the hydrothermal reaction is 160-230°C, and the reaction time is 12-24h; The calcination temperature is 450-700° C. and the calcination time is 0.5-5 h.

2. The method for preparing the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material according to claim 1, characterized in that: The copper source is copper acetate; the solvent II is water or ethanol.

3. The method for preparing the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material according to claim 2, characterized in that: In the step (2), the mass ratio of molybdenum disulfide to copper source is 1:(1-12); the concentration of molybdenum disulfide in solvent II is 0.05-0.2 mmol / ml.

4. The method for preparing the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material according to claim 3, characterized in that: The microwave-assisted conditions are: reaction temperature of 80-110° C., microwave power of 100-1000 W, and time of 1-20 minutes.

5. The CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material prepared by the method according to any one of claims 1 to 4.

6. Application of the CuO / MoS2 / CuMoO4 multi-level structure nanocomposite material according to claim 5 in gas concentration detection.

Citation Information

Patent Citations

  • Metal oxide / graphene nano-structure material prepared in microwave-assisted manner, and preparation method thereof

    CN111039283A

  • Preparation method of microspheric CuS-MoS2 composite material

    CN112110489A